Bio-based polymer composite board and preparation method thereof
By modifying polyethylene terephthalate and chitosan to encapsulate diatomaceous earth, a bio-based polymer composite plate with excellent flame retardant, anti-aging and impact resistance was prepared, and polyterephthalate was solved The flammability, rapid combustion and ultraviolet degradation of ethylene glycol formate in composite sheets.
Patent Information
- Application Number
- CN202411689006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-11
AI Technical Summary
Polyethylene terephthalate has high flammability, fast combustion speed and melt dripping in composite sheets, and is prone to ultraviolet degradation, resulting in a shorter service life.
Terminal carboxysiloxane oligomers were prepared by reacting 1,3,5,7-tetramethylcyclotetrasiloxane with 1,3-bis(3-carboxypropyl)tetramethyldisilane and with Polycondensation of terephthalic acid and ethylene glycol to obtain silicone polyethylene terephthalate, which reacts with hydroquinone monomethacrylate and para-aldehyde benzoic acid to produce modified polyterephthalate Ethylene formate. At the same time, chitosan is wrapped in diatomaceous earth to produce modified chitosan, and mixed with modified polyethylene terephthalate to form a bio-based polymer composite plate.
It improves the flame retardant, anti-aging and impact resistance of bio-based polymer composite panels, extends the service life and reduces safety hazards.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a bio-based polymer composite board and a preparation method thereof. Background Art
[0002] As people's requirements for living environment increase, the formaldehyde emission of adhesives in composite panels is gradually becoming a focus of attention. Bio-based materials such as chitosan, cellulose, diatomaceous earth, etc. are not only widely available, but also renewable and degradable. These biomass matrices are combined with polymer matrices to form composite materials with excellent performance.
[0003] Polyethylene terephthalate, as a high-quality thermoplastic, has great potential in the field of composite panels due to its excellent transparency, non-toxicity and chemical corrosion resistance. As a matrix material, it not only has good formability and processability, but also maintains the lightness and strength of the material, and can be recycled after processing. However, polyethylene terephthalate also has defects that cannot be ignored, such as high flammability, fast burning speed and severe melt dripping, which all constitute potential safety hazards. In addition, polyethylene terephthalate is prone to degradation when exposed to ultraviolet rays for a long time, resulting in a significant shortening of its service life. Therefore, modifying polyethylene terephthalate to improve its anti-aging and flame retardant properties is an urgent problem to be solved. Summary of the invention
[0004] The object of the present invention is to provide a bio-based polymer composite board and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A bio-based polymer composite board is prepared by mixed extrusion and compression molding of modified polyethylene terephthalate, modified chitosan and dimethyl phosphite.
[0007] As an optimization, the modified polyethylene terephthalate is prepared by adding organosilicon polyethylene terephthalate and hydroquinone monomethacrylate to obtain pre-modified polyethylene terephthalate, which is prepared by a substitution reaction between the pre-modified polyethylene terephthalate and 4-formylbenzoyl chloride.
[0008] As an optimization, the organosilicon polyethylene terephthalate is prepared by esterification and polycondensation of terminal hydroxyl siloxane oligomers with terephthalic acid and ethylene glycol.
[0009] As an optimization, the terminal hydroxyl siloxane oligomer is prepared by reacting 1,3,5,7-tetramethylcyclotetrasiloxane with 1,3-bis(3-carboxypropyl)tetramethyldisilane.
[0010] As an optimization, the modified chitosan is prepared by chitosan encapsulating diatomaceous earth.
[0011] A method for preparing a bio-based polymer composite board comprises the following preparation steps:
[0012] (1) Terephthalic acid, ethylene glycol, carboxyl-terminated siloxane oligomer, and antimony trioxide are uniformly mixed in a mass ratio of 1:(3-5):(0.12-0.15):(0.03-0.04), nitrogen is charged into a reaction kettle, and the mixture is reacted at 200-250° C. and a pressure of 320-340 kPa for 2 h, and then reacted at 280-290° C. for 1 h under a vacuum state, and then cooled to room temperature after returning to normal pressure, the reaction kettle is opened, filtered, washed with deionized water and anhydrous ethanol for 2-3 times each, and dried in a vacuum oven at 90° C. for 12 h to obtain silicone polyethylene terephthalate;
[0013] (2) Silicone polyethylene terephthalate, hydroquinone monomethacrylate, chloroplatinic acid and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1: (0.5-0.8): (0.01-0.02): (10-20), stirred at 70-80°C and 300-500 r / min for 4-6 hours, added with deionized water for 30-40 minutes, filtered, washed with anhydrous ethanol for 3-5 times, placed in a vacuum drying oven at 80-100°C for 8-12 hours, and obtained pre-modified poly(p-phenylene) Ethylene glycol dicarboxylate; pre-modified polyethylene terephthalate, paraformylbenzoic acid, phosphorus oxychloride, zinc chloride, and cyclopentane sulfone are uniformly mixed in a mass ratio of 1: (2-3): (1.5-2): (2-2.5): (10-20), stirred at 70-80° C. and 200-300 r / min for 1-2 hours, poured into ice water after cooling, filtered, washed with deionized water for 3-5 times, placed in a vacuum oven at 100-120° C. and dried for 10-12 hours to obtain modified polyethylene terephthalate;
[0014] (3) Chitosan, diatomaceous earth, deionized water and concentrated sulfuric acid (mass fraction 95-98%) are mixed and stirred in a mass ratio of 1: (3-4): (50-80): (0.1-0.3), stirred and reacted at 20-25°C and 200-300 r / min for 2 h, filtered, washed with deionized water and anhydrous ethanol 2-3 times each, and frozen at -20°C for 4 h, and then transferred to a freeze dryer for freeze drying at -78°C and 50 Pa for 24 h to obtain modified chitosan; the modified chitosan is Ethylene glycol terephthalate, modified chitosan and dimethyl phosphite are added into a twin-screw extruder in a mass ratio of 2:(1-1.2):(1.2-1.3) for melt blending. The temperature of zone 1 is 180-190°C, the temperature of zone 2 is 220-230°C, the temperature of zone 3 is 250-280°C, the screw speed is 80-100 r / min, extruded, poured into a mold, hot pressed at 250°C, 100-150 MPa for 30 minutes, naturally cooled, taken out, and a bio-based polymer composite board is obtained.
[0015] As an optimization, the preparation method of the terminal carboxyl siloxane oligomer described in step (1) is as follows: 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-carboxypropyl)tetramethyldisilane and tetramethylammonium hydroxide are uniformly mixed in a mass ratio of 1:(0.1-0.2):(0.01-0.02), stirred at 70-90°C and 300-500r / min for 30-40min, and allowed to stand at 140-150°C for 30min to obtain a terminal carboxyl siloxane oligomer.
[0016] As an optimization, the reaction process of the silicone polyethylene terephthalate in step (1) is:
[0017]
[0018] As an optimization, the reaction process of the modified polyethylene terephthalate in step (2) is as follows:
[0019]
[0020]
[0021] As an optimization, the reaction process of the bio-based polymer composite board in step (3) is as follows:
[0022]
[0023] R is H or
[0024]
[0025] As an optimization, the deacetylation degree of the chitosan in step (3) is 90%.
[0026] As an optimization, the specification of the diatomaceous earth in step (3) is 300 mesh.
[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0028] The present invention relates to the technical field of polymer materials when preparing a bio-based polymer composite board. When preparing a bio-based polymer composite board, the present invention reacts 1,3,5,7-tetramethylcyclotetrasiloxane with 1,3-bis(3-carboxypropyl)tetramethyldisilane to obtain a carboxyl-terminated siloxane oligomer, which is then polycondensed with terephthalic acid and ethylene glycol to obtain organosilicon polyethylene terephthalate, which is successively reacted with hydroquinone monomethacrylate and paraformylbenzoic acid to obtain modified polyethylene terephthalate; chitosan is wrapped around diatomaceous earth to obtain modified chitosan; the modified polyethylene terephthalate, the modified chitosan and dimethyl phosphite are mixed and extruded and molded to obtain a bio-based polymer composite board. The bio-based polymer composite board prepared by the present invention has excellent flame retardant, anti-aging and impact resistance.
[0029] Firstly, 1,3,5,7-tetramethylcyclotetrasiloxane is reacted with 1,3-bis(3-carboxypropyl)tetramethyldisilane to obtain terminal carboxyl siloxane oligomers, which are then polycondensed with terephthalic acid and ethylene glycol to obtain silicone polyethylene terephthalate. The introduction of siloxy groups into the main chain of polyethylene terephthalate not only increases the impact resistance, but also forms a carbon protective layer at high temperature to terminate the chain reaction, thus giving the bio-based polymer composite board excellent flame retardant properties.
[0030] Secondly, silicone polyethylene terephthalate is added with hydroquinone monomethacrylate and then substituted with p-formylbenzoic acid to obtain modified polyethylene terephthalate. Silicon hydrogen and acrylate groups are added first, and the hydrogen on the hydroxyl ortho-benzene ring is replaced by the formic acid of p-formylbenzoic acid. A structure containing a hydroxyl group ortho to the carbonyl group is introduced into the side chain. The carbonyl and hydroxyl groups in the structure can form a chelate ring. When absorbing ultraviolet rays, the hydrogen bonds are destroyed, the chelate ring opens, and the energy of the ultraviolet rays is immediately converted into heat energy and slowly released, giving the bio-based polymer composite board excellent anti-aging properties.
[0031] Finally, chitosan is wrapped with diatomaceous earth to obtain modified chitosan, which is then reacted with modified polyethylene terephthalate to form a Schiff base structure. Chitosan is biodegradable and has the advantages of sterilization and antiseptic properties. Diatomaceous earth is a heat-insulating, noise-reducing, fire-retardant material that can improve the impact resistance and flame retardancy of chitosan. The phosphorus and hydrogen of dimethyl phosphite are adsorbed and combined with the Schiff base, and the introduced phosphate groups can form a protective carbon layer during combustion to prevent the transfer of oxygen and heat, thereby improving the flame retardant properties of the flame-retardant bio-based polymer composite board. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] In order to more clearly illustrate the method provided by the present invention, it is now described in detail through the following examples.
[0034] Example 1
[0035] A method for preparing a bio-based polymer composite board mainly includes the following preparation steps:
[0036] (1) 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-carboxypropyl)tetramethyldisilane and tetramethylammonium hydroxide were mixed uniformly in a mass ratio of 1:0.1:0.01, stirred at 70°C and 300 r / min for 30 min, and allowed to stand at 140°C for 30 min to obtain a terminal carboxyl siloxane oligomer; terephthalic acid, ethylene glycol, terminal carboxyl siloxane oligomer and antimony trioxide were mixed uniformly in a mass ratio of 1:3:0.12:0.03, nitrogen was charged into a reactor, reacted at 200°C and 320 kPa for 2 h, and then reacted at 280°C for 1 h under vacuum, returned to normal pressure and cooled to room temperature, opened the reactor, filtered, washed twice with deionized water and anhydrous ethanol, and dried at 90°C in a vacuum oven for 12 h to obtain silicone polyethylene terephthalate;
[0037] (2) Organic silicon polyethylene terephthalate, hydroquinone monomethacrylate, chloroplatinic acid, and dimethyl sulfoxide were mixed in a mass ratio of 1:0.5:0.01:10, stirred at 70°C and 300 r / min for 4 h, added with deionized water for ultrasonic treatment for 30 min, filtered, washed with anhydrous ethanol for 3 times, and dried in a vacuum drying oven at 80°C for 8 h to obtain pre-modified polyethylene terephthalate; pre-modified polyethylene terephthalate, paraformylbenzoic acid, phosphorus oxychloride, zinc chloride, and cyclopentane sulfone were mixed in a mass ratio of 1:2:1.5:2:10, stirred at 70°C and 200 r / min for 1 h, poured into ice water after cooling, filtered, washed with deionized water for 3 times, and dried in a vacuum drying oven at 100°C for 10 h to obtain modified polyethylene terephthalate;
[0038] (3) Chitosan, diatomaceous earth, deionized water and 95% concentrated sulfuric acid were mixed and stirred in a mass ratio of 1:3:50:0.1, stirred and reacted at 20°C and 200 r / min for 2 h, filtered, washed twice with deionized water and anhydrous ethanol, and frozen at -20°C for 4 h, then transferred to a freeze dryer and freeze-dried at -78°C and 50 Pa for 24 h to obtain modified chitosan; modified polyethylene terephthalate, modified chitosan and dimethyl phosphite were added into a twin-screw extruder in a mass ratio of 2:1:1.2 for melt blending, the temperature of the first zone was 180°C, the temperature of the second zone was 220°C, the temperature of the third zone was 250°C, the screw speed was 80 r / min, extruded, poured into a mold, hot pressed at 250°C and 100 MPa for 30 min, naturally cooled, and then taken out to obtain a bio-based polymer composite board.
[0039] Example 2
[0040] A method for preparing a bio-based polymer composite board mainly includes the following preparation steps:
[0041] (1) 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-carboxypropyl)tetramethyldisilane and tetramethylammonium hydroxide were mixed uniformly in a mass ratio of 1:0.15:0.018, stirred at 80°C and 400 r / min for 35 min, and allowed to stand at 145°C for 30 min to obtain a terminal carboxyl siloxane oligomer; terephthalic acid, ethylene glycol, terminal carboxyl siloxane oligomer and antimony trioxide were mixed uniformly in a mass ratio of 1:4.5:0.13:0.036, nitrogen was charged into a reactor, reacted at 240°C and 330 kPa for 2 h, and then reacted at 285°C for 1 h under vacuum, and then cooled to room temperature after returning to normal pressure, opened the reactor, filtered, washed with deionized water and anhydrous ethanol 3 times each, and dried at 90°C in a vacuum oven for 12 h to obtain silicone polyethylene terephthalate;
[0042] (2) Organic silicon polyethylene terephthalate, hydroquinone monomethacrylate, chloroplatinic acid, and dimethyl sulfoxide were mixed in a mass ratio of 1:0.7:0.015:15, stirred at 78°C and 400 r / min for 4.5 h, added with deionized water for ultrasonic treatment for 35 min, filtered, washed with anhydrous ethanol 4 times, and dried in a vacuum drying oven at 90°C for 10 h to obtain pre-modified polyethylene terephthalate; pre-modified polyethylene terephthalate, paraformylbenzoic acid, phosphorus oxychloride, zinc chloride, and cyclopentane sulfone were mixed in a mass ratio of 1:2.5:1.7:2.3:15, stirred at 75°C and 250 r / min for 1.5 h, poured into ice water after cooling, filtered, washed with deionized water 4 times, and dried at 110°C for 11 h to obtain modified polyethylene terephthalate;
[0043] (3) Chitosan, diatomaceous earth, deionized water and 96% concentrated sulfuric acid were mixed and stirred in a mass ratio of 1:3.5:70:0.2, stirred and reacted at 23°C and 250 r / min for 2 h, filtered, washed twice with deionized water and anhydrous ethanol, and frozen at -20°C for 4 h, then transferred to a freeze dryer and freeze-dried at -78°C and 50 Pa for 24 h to obtain modified chitosan; modified polyethylene terephthalate, modified chitosan and dimethyl phosphite were added into a twin-screw extruder in a mass ratio of 2:1.1:1.25 for melt blending, the temperature of the first zone was 185°C, the temperature of the second zone was 225°C, the temperature of the third zone was 270°C, the screw speed was 90 r / min, extruded, poured into a mold, hot pressed at 250°C and 130 MPa for 30 min, naturally cooled, and then taken out to obtain a bio-based polymer composite board.
[0044] Example 3
[0045] A method for preparing a bio-based polymer composite board mainly includes the following preparation steps:
[0046] (1) 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-carboxypropyl)tetramethyldisilane and tetramethylammonium hydroxide were mixed uniformly in a mass ratio of 1:0.2:0.02, stirred at 90°C and 500 r / min for 40 min, and allowed to stand at 150°C for 30 min to obtain a terminal carboxyl siloxane oligomer; terephthalic acid, ethylene glycol, terminal carboxyl siloxane oligomer and antimony trioxide were mixed uniformly in a mass ratio of 1:5:0.15:0.04, nitrogen was charged into a reactor, reacted at 250°C and 340 kPa for 2 h, and then reacted at 290°C under vacuum for 1 h, and then cooled to room temperature after returning to normal pressure, opened the reactor, filtered, washed with deionized water and anhydrous ethanol for 3 times each, and dried in a vacuum oven at 90°C for 12 h to obtain silicone polyethylene terephthalate;
[0047] (2) Organic silicon polyethylene terephthalate, hydroquinone monomethacrylate, chloroplatinic acid, and dimethyl sulfoxide were mixed uniformly in a mass ratio of 1:0.8:0.02:20, stirred at 80°C and 500 r / min for 6 h, added with deionized water for ultrasonic treatment for 40 min, filtered, washed with anhydrous ethanol 5 times, and dried in a vacuum drying oven at 100°C for 12 h to obtain pre-modified polyethylene terephthalate; pre-modified polyethylene terephthalate, paraformylbenzoic acid, phosphorus oxychloride, zinc chloride, and cyclopentane sulfone were mixed uniformly in a mass ratio of 1:3:2:2.5:20, stirred at 80°C and 300 r / min for 2 h, poured into ice water after cooling, filtered, washed with deionized water 5 times, and dried at 120°C for 12 h to obtain modified polyethylene terephthalate;
[0048] (3) Chitosan, diatomaceous earth, deionized water and 98% concentrated sulfuric acid were mixed and stirred in a mass ratio of 1:4:80:0.3, stirred and reacted at 25°C and 300 r / min for 2 h, filtered, washed with deionized water and anhydrous ethanol three times each, and frozen at -20°C for 4 h, then transferred to a freeze dryer and freeze-dried at -78°C and 50 Pa for 24 h to obtain modified chitosan; modified polyethylene terephthalate, modified chitosan and dimethyl phosphite were added into a twin-screw extruder in a mass ratio of 2:1.2:1.3 for melt blending, the temperature of the first zone was 190°C, the temperature of the second zone was 230°C, the temperature of the third zone was 280°C, the screw speed was 100 r / min, extruded, poured into a mold, hot pressed at 250°C and 150 MPa for 30 min, naturally cooled, and then taken out to obtain a bio-based polymer composite board.
[0049] Comparative Example 1
[0050] The difference between the bio-based polymer composite board of Comparative Example 1 and Example 2 is only in step (1), which is modified as follows: terephthalic acid, ethylene glycol, and antimony trioxide are mixed uniformly in a mass ratio of 1:4.5:0.036, nitrogen is charged into a reactor, and the reaction is carried out at 240° C. and a pressure of 330 kPa for 2 h, and then at 285° C. under a vacuum state for 1 h, and then cooled to room temperature after returning to normal pressure, the reactor is opened, filtered, washed with deionized water and anhydrous ethanol 3 times each, and placed in a vacuum oven at 90° C. for 12 h to obtain organosilicon polyethylene terephthalate. The remaining steps are the same as those of Example 2.
[0051] Comparative Example 2
[0052] The difference between the bio-based polymer composite board of Comparative Example 2 and Example 2 is only in step (2), which is modified as follows: organic silicon polyethylene terephthalate, 4-vinylbenzaldehyde, chloroplatinic acid, and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1:0.7:0.015:15, stirred at 78°C and 400r / min for 4.5h, added with deionized water and ultrasonicated for 35min, filtered, washed with anhydrous ethanol 4 times, placed in a vacuum drying oven at 90°C for 10h, and prepared modified polyethylene terephthalate. The remaining steps are the same as those of Example 2.
[0053] Comparative Example 3
[0054] The difference between the bio-based polymer composite board of Comparative Example 3 and Example 2 is that step (3) is performed, and step (3) is modified as follows: chitosan, diatomaceous earth, deionized water and 96% concentrated sulfuric acid are mixed and stirred in a mass ratio of 1:3.5:70:0.2, stirred and reacted at 23°C and 250r / min for 2h, filtered, washed twice with deionized water and anhydrous ethanol, and frozen at -20°C for 4h, and then transferred to a freeze dryer at -78 ℃ and 50Pa, freeze-dried for 24h to obtain modified chitosan; modified polyethylene terephthalate and modified chitosan were added into a twin-screw extruder at a mass ratio of 2:1.1 for melt blending, with the temperature of the first zone at 185℃, the temperature of the second zone at 225℃, the temperature of the third zone at 270℃, and the screw speed at 90r / min, extruded, poured into a mold, hot-pressed at 250℃, 130MPa for 30min, naturally cooled, and taken out to obtain a bio-based polymer composite board. The remaining steps are the same as in Example 2.
[0055] Comparative Example 4
[0056] The difference between the bio-based polymer composite board of Comparative Example 4 and Example 2 is only in step (3), which is modified as follows: adding modified polyethylene terephthalate, chitosan, and dimethyl phosphite in a mass ratio of 2:1.1:1.25 to a twin-screw extruder for melt blending, with a temperature of 185°C in the first zone, 225°C in the second zone, and 270°C in the third zone, and a screw speed of 90 r / min, extruding, pouring into a mold, hot pressing at 250°C, 130 MPa, for 30 min, and naturally cooling, taking out, and obtaining a bio-based polymer composite board. The remaining steps are the same as those in Example 2.
[0057] Test Example 1
[0058] Flame retardant performance test
[0059] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406.2, and the limiting oxygen index of the examples and comparative examples was tested. The results are shown in Table 1.
[0060] Table 1
[0061] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 37.4 Comparative Example 1 21.9 Example 2 38.7 Comparative Example 2 38.6 Example 3 38.1 Comparative Example 3 25.4 Comparative Example 4 32.1
[0062] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the bio-based polymer composite board prepared by the present invention has good flame retardant properties.
[0063] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1. This indicates that 1,3,5,7-tetramethylcyclotetrasiloxane is reacted with 1,3-bis(3-carboxypropyl)tetramethyldisilane to obtain a terminal carboxyl siloxane oligomer, which is esterified and polycondensed with phthalic acid and ethylene glycol to form organosilicon polyethylene terephthalate, and a silicon-containing carbon barrier layer is formed when the siloxy groups burn, isolating the contact with oxygen, and giving the bio-based polymer composite board good flame retardancy.
[0064] The limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3. This indicates that the modified chitosan and the modified polyethylene terephthalate react to form a Schiff base structure and the phosphorus-hydrogen adsorption of dimethyl phosphite, introducing a phosphite structure, and giving the bio-based polymer composite board good flame retardancy.
[0065] The limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 4. This indicates that chitosan is coated with diatomaceous earth to obtain modified chitosan, and diatomaceous earth gives the bio-based polymer composite board good flame retardancy.
[0066] Test Example 2
[0067] Anti-aging performance test
[0068] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T1040.1, and their tensile strength was tested. The examples and comparative examples were placed in a xenon lamp accelerated aging test box with the temperature set to 50°C, humidity 60%, radiation intensity 550W / m2, and aging time 240h to test their tensile strength. The tensile performance reduction rate of the examples and comparative examples before and after the photothermal aging treatment was calculated, and the tensile performance reduction rate = 1-tensile strength after aging / initial tensile strength. The results are shown in Table 2.
[0069] Table 2
[0070] Tensile performance decrease rate (%) Tensile performance decrease rate (%) Example 1 2.05 Comparative Example 1 9.73 Example 2 1.67 Comparative Example 2 15.39 Example 3 2.21 Comparative Example 3 13.21 Comparative Example 4 6.16
[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the bio-based polymer composite board prepared by the present invention has good anti-aging performance.
[0072] By comparison, the change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 1, which shows that 1,3,5,7-tetramethylcyclotetrasiloxane is reacted with 1,3-bis(3-carboxypropyl)tetramethyldisilane to obtain terminal carboxyl siloxane oligomers, and the terminal carboxyl siloxane oligomers are esterified and polycondensed with phthalic acid and ethylene glycol to form silicone polyethylene terephthalate. The siloxy group bond energy is large and is not easy to break when absorbing ultraviolet rays, thereby enhancing the anti-aging properties of the bio-based polymer composite board.
[0073] The change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 2, indicating that the o-hydroxybenzophenone structure formed by hydroquinone monomethacrylate and p-formylbenzoic acid has a good ultraviolet absorption effect, giving the bio-based polymer composite board good anti-aging properties.
[0074] The change rate of tensile strength of Examples 1 to 3 is less than that of Comparative Example 3, indicating that the modified polyethylene terephthalate and modified chitosan are reacted to form a Schiff base structure, the phosphorus hydrogen of dimethyl phosphite is adsorbed and combined with the Schiff base, and the introduced phosphate group serves as an auxiliary antioxidant, thereby improving the anti-aging performance of the bio-based polymer composite board.
[0075] The change rates of the tensile strength of Examples 1 to 3 are less than that of Comparative Example 4, indicating that chitosan encapsulates diatomaceous earth and enhances the anti-aging performance of the bio-based polymer composite board.
[0076] Test Example 3
[0077] Impact resistance test
[0078] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T1043, and the examples and comparative examples were placed in a simply supported beam impact tester, with an impact speed of 2.9 m / s and a distance of 221 mm from the center of the pendulum to the center of the specimen, to test their impact strength. The results are shown in Table 3.
[0079] Table 3
[0080] <![CDATA[Notched impact strength (kJ / m 2 )]]> <![CDATA[Notched impact strength (kJ / m 2 )]]> Example 1 212 Comparative Example 1 180 Example 2 225 Comparative Example 2 223 Example 3 220 Comparative Example 3 224 Comparative Example 4 142
[0081] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the bio-based polymer composite board prepared by the present invention has good impact resistance.
[0082] By comparison, the unnotched simply supported beam impact strength of Examples 1 to 3 is greater than that of Comparative Example 1, which shows that 1,3,5,7-tetramethylcyclotetrasiloxane is reacted with 1,3-bis(3-carboxypropyl)tetramethyldisilane to obtain terminal carboxyl siloxane oligomers, and the terminal carboxyl siloxane oligomers are esterified and polycondensed with phthalic acid and ethylene glycol to form organosilicon polyethylene terephthalate. The introduction of siloxy groups gives the bio-based polymer composite board impact resistance.
[0083] The unnotched simply supported beam impact strength of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that chitosan is encapsulated with diatomaceous earth to prepare modified chitosan, and the modification of diatomaceous earth gives the bio-based polymer composite board impact resistance.
[0084] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A bio-based polymer composite board, characterized in that: The bio-based polymer composite board is made by mixing modified polyethylene terephthalate, modified chitosan and dimethyl phosphite and extruding them through compression molding; The modified polyethylene terephthalate is prepared by adding organosilicon polyethylene terephthalate to hydroquinone monomethacrylate to obtain pre-modified polyethylene terephthalate, and the pre-modified polyethylene terephthalate is prepared by a substitution reaction with para-formylbenzoic acid; The organosilicon polyethylene terephthalate is prepared by polycondensation of carboxyl-terminated siloxane oligomers with terephthalic acid and ethylene glycol through esterification reaction; The carboxyl-terminated siloxane oligomer is prepared by reacting 1,3,5,7-tetramethylcyclotetrasiloxane with 1,3-bis(3-carboxypropyl)tetramethyldisilane; The modified chitosan is prepared by wrapping diatomaceous earth with chitosan.
2. A method for preparing a bio-based polymer composite board, characterized in that: The method comprises the following preparation steps: (1) Terephthalic acid, ethylene glycol, carboxyl-terminated siloxane oligomer, and antimony trioxide are uniformly mixed in a mass ratio of 1:(3-5):(0.12-0.15):(0.03-0.04), nitrogen is charged into a reaction kettle, and the mixture is reacted at 200-250° C. and a pressure of 320-340 kPa for 2 h, and then reacted at 280-290° C. for 1 h under a vacuum state, and then cooled to room temperature after returning to normal pressure, the reaction kettle is opened, filtered, washed with deionized water and anhydrous ethanol for 2-3 times each, and dried in a vacuum oven at 90° C. for 12 h to obtain silicone polyethylene terephthalate; (2) Silicone polyethylene terephthalate, hydroquinone monomethacrylate, chloroplatinic acid and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1: (0.5-0.8): (0.01-0.02): (10-20), stirred at 70-80°C and 300-500 r / min for 4-6 hours, added with deionized water for 30-40 minutes, filtered, washed with anhydrous ethanol for 3-5 times, placed in a vacuum drying oven at 80-100°C for 8-12 hours, and obtained pre-modified poly(p-phenylene) Ethylene glycol dicarboxylate; pre-modified polyethylene terephthalate, paraformylbenzoic acid, phosphorus oxychloride, zinc chloride, and cyclopentane sulfone are uniformly mixed in a mass ratio of 1: (2-3): (1.5-2): (2-2.5): (10-20), stirred at 70-80° C. and 200-300 r / min for 1-2 hours, poured into ice water after cooling, filtered, washed with deionized water for 3-5 times, placed in a vacuum oven at 100-120° C. and dried for 10-12 hours to obtain modified polyethylene terephthalate; (3) Chitosan, diatomaceous earth, deionized water and concentrated sulfuric acid (mass fraction 95-98%) are mixed and stirred in a mass ratio of 1: (3-4): (50-80): (0.1-0.3), stirred and reacted at 20-25°C and 200-300 r / min for 2 h, filtered, washed with deionized water and anhydrous ethanol 2-3 times each, and frozen at -20°C for 4 h, and then transferred to a freeze dryer for freeze drying at -78°C and 50 Pa for 24 h to obtain modified chitosan; the modified chitosan is Ethylene glycol terephthalate, modified chitosan and dimethyl phosphite are added into a twin-screw extruder in a mass ratio of 2:(1-1.2):(1.2-1.3) for melt blending. The temperature of zone 1 is 180-190°C, the temperature of zone 2 is 220-230°C, the temperature of zone 3 is 250-280°C, the screw speed is 80-100 r / min, extruded, poured into a mold, hot pressed at 250°C, 100-150 MPa for 30 minutes, naturally cooled, taken out, and a bio-based polymer composite board is obtained.
3. The method for preparing a bio-based polymer composite board according to claim 2, characterized in that: The preparation method of the terminal carboxyl siloxane oligomer described in step (1) is as follows: 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-carboxypropyl)tetramethyldisilane and tetramethylammonium hydroxide are uniformly mixed in a mass ratio of 1:(0.1-0.2):(0.01-0.02), stirred at 70-90° C. and 300-500 r / min for 30-40 min, and allowed to stand at 140-150° C. for 30 min to obtain the terminal carboxyl siloxane oligomer.
4. The method for preparing a bio-based polymer composite board according to claim 2, characterized in that: The reaction process of the silicone polyethylene terephthalate in step (1) is as follows:
5. The method for preparing a bio-based polymer composite board according to claim 2, characterized in that: The reaction process of the modified polyethylene terephthalate in step (2) is as follows:
6. The method for preparing a bio-based polymer composite board according to claim 2, characterized in that: The reaction process of the bio-based polymer composite board in step (3) is as follows: R is H or